The Combustion Characteristics of Biomass Stove with Preheated-Air by Porous Medium - Laodee , P; Setthapun, W; Sawatdeenarunat, C (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
This study aims to characterize the combustion of the biomass stove filled with a porous medium for air pre-heating to enhance the biomass decomposition. An equivalence ratio, one of the important parameters for the combustion, was investigated to evaluate the completeness of the combustion process. Thermal efficiency was used as the indicator to reflect the performance of the biomass stove. Which was divided into two parts namely the pre-combustion (PCC) and the combustion chamber (CC). The CC volume was 28 liters for fuel storage, and it was insulated for reducing heat loss. The stove was made of 2 mm steel plate and the porous medium was a round-shape ceramic with a diameter of 10 mm. The boiling test was performed using corn cobs as a single solid fuel to boil water in the vessel. The temperature of the stove was measured using a thermocouple Type-K and a data recorder was used to collect the experimental data. The airflow rate was determined using an airflow meter and the fuel consumption rate was calculated using the aforementioned experimental data. Finally, the designed biomass stove will be demonstrated at the community to simultaneously enhance the community-scale energy and reduce the environmental issues.